A novel CC chemokine ligand 2 like gene from ayu Plecoglossus altivelis is involved in the innate immune response against to Vibrio anguillarum. Issue 87 (April 2019) - Yu, Li; Li, Chang-Hong; Chen, Jiong
Abstract: Chemokine (CC motif) ligand 2 (CCL2), also known as monocyte chemoattractant protein 1 (MCP-1), is one of the key chemokines that regulate migration and infiltration of monocytes/macrophages (MO/MФ) in mammals. However, the functional repertoire of fish CCL2 remains unclear. Here, we identified a cDNA sequence encoding a novel CCL2-like protein (PaCCL2L) in ayu, Plecoglossus altivelis . Sequence analysis revealed that PaCCL2L grouped with CCL2 homologs, and is most closely related to Mexican tetra ( Astyanax mexicanus ) and zebrafish ( Danio rerio ) homologs. PaCCL2 transcripts were expressed in all tested tissues from healthy ayu, with the highest level in the spleen. Upon Vibrio anguillarum infection, PaCCL2L transcripts increased significantly in tested tissues, including the liver, spleen, and head kidney. We then produced the recombinant PaCCL2L mature peptide (rPaCCL2L) by prokaryotic expression and generated the corresponding antibodies (anti-PaCCL2L). A significant increase in PaCCL2L protein and mRNA expression was observed in ayu MO/MФ following V. anguillarum challenge. Intraperitoneal injection of rPaCCL2L resulted in significantly improved survival and reduced tissue bacterial load in V. anguillarum -infected ayu. rPaCCL2L had a positive effect on the chemotaxis of MO/MΦ and neutrophils both in vitro and in vivo . Meanwhile, rPaCCL2L exhibited a positive effect on the chemotaxis of LPS-stimulated MO/MΦ (M1 type) in vitro, whereas it exhibited no chemotaxis effect on cAMP-stimulated MO/MΦ (M2 type). In addition, rPaCCL2L treatment exhibited an enhanced effect on MO/MΦ phagocytosis, bacterial killing, respiratory burst, and mRNA expression of proinflammatory cytokines, whereas anti-PaCCL2L treatment had an inhibitory effect. Our study demonstrates that PaCCL2L might play a role in the immune response of ayu against V. anguillarum infection through chemotactic recruitment and activation of MO/MΦ. Highlights: We characterized a CCL2-like gene (PaCCL2L) from ayu. PaCCL2L expression responded to Vibrio anguillarum infection. PaCCL2L increased survival and decreased bacterial load of ayu during infection. PaCCL2L induced chemotaxis of resting and M1-type MO/MΦ, and neutrophils in vitro . PaCCL2L treatment induced ayu MO/MΦ activation in vitro .